(untitled) (Tikrit Journal of Pharmaceutical Sciences, 2023)
Intramedullary spinal epidermoid cysts are rare, with only few cases having been reported in the literature. A case of a eighteen months-old male child who presented with chronic progressive qaudriparesis and urine incontinance . Magnetic resonance imaging of the spine revealed an intramedullary epidermoid cyst at cervicomedullary at level c2-c3. Near-total excision of the tumor was performed. Histopathological report confirmed the diagnosis of epidermoid cyst. The patient showed progressive recovery.